Proposal of a P300-based BCI Speller using a predictive Text system - Ron-Angevin, Ricardo; Da Silva-Sauer, Leandro (SCITEPRESS, 2013)
This paper presents a P300-based BCI speller system that uses a virtual 4 x 3 keyboard based on the T9 interface developed on mobile phones in order to increase the writing speed. To validate the effectiveness of the proposed BCI, we compared it with two adaptations of the classical Farwell and Donchin speller, which is based on a 6 x 6 symbol matrix. Three healthy subjects took part in the experiment. The preliminary results confirm the effectiveness of T9-based speller, since the time needed to spell words and complete sentences was considerably reduced.
Keywords: Circuitos de interfaces; Interfaces de ordenadores; Brain Computer Interface (BCI); P300; Speller; T9 interface